DIREITO À EDUCAÇÃO POR MEIO DAS AÇÕES AFIRMATIVAS PARA O ENSINO SUPERIOR: garantia de exercício de cidadania pelo acesso/permanência nas Universidades Federais no Mato Grosso do Sul no período de 2018 a 2021. - Maicon Guilland Veiga (2022)
The right to education is an essential and fundamental right for the development of the individual as a citizen while belonging to society. Hereupon, the guarantee of this right meets the demands of social development, awakening the possibility of social transformation within its sphere of action. The present study aims to analyze the issues related to affirmative actions and the right to education, ensuring citizenship rights, access, and permanence of students who enroll through affirmative action policies in the Federal Universities of Mato Grosso do Sul from 2018 to 2021. At first, will analyze conceptual issues related to education rights, as well as its history to the present day. An analysis into the legal sphere, regarding the rights to access a post-secondary education, considering the concept of democracy, education, education rights, citizenship rights and affirmative actions, will take place. Therefore, the concepts of social justice approached by Rawls (2009) and the effects that are reflected when speaking about affirmative actions and education, will be brought up. When analyzing these concepts and their applicability concerning public post-secondary education institutions, as well as the analysis of the current laws that protect individuals, the theme becomes important. Contributions from studies directly related to the social environment help in the proposal of public policies of affirmative actions, in allowing the reduction of social inequalities and in providing the development of society itself; in addition to contributing to the educational scope, mapping and analyzing the actions adopted by the Federal Universities of Mato Grosso do Sul. Thus, through the methodology based on bibliographic reviews of qualitative and descriptive character, it will bring theoretical basis in the area of concentration of the study. As a result of the statistical analyzes carried out in this study, it demonstrates that affirmative actions favor the access and permanence of academics in public post-secondary institutions highlighting their importance, as well as certifying that social, economic, racial and other factors, are taken into account, ensuring social inclusion.